The Effect of Shopping Lifestyle, Fashion Engagement, and Hedonic Shopping on E-Commerce with Impulsive Purchasing as a Mediating Variable - Fatiani, Kurunul; Sutawidjaya, Ahmad Hidayat; Mariam, Siti; Ramli, Abdul Haeba (Neo Journal of economy and social humanities, 2025)
In recent years, online shopping activities in the fashion sector have shown a significant increase. This shift has been further accelerated by the COVID-19 pandemic, which encouraged consumers to move from conventional shopping to e-commerce platforms that are considered more practical, safe, and accessible. The transformation of consumption patterns has strengthened the transition toward digital shopping, particularly for fashion products. This study aims to examine the influence of shopping lifestyle, fashion involvement, and hedonic orientation on impulsive buying behavior. Furthermore, it investigates the mediating role of impulsive buying in enhancing the intention to use e-commerce. A quantitative survey method was employed, with data analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The sample consisted of 130 respondents residing in Tangerang Regency who actively purchase fashion items through Shopee. The findings reveal that shopping lifestyle, fashion involvement, and hedonic orientation have a positive and significant effect on impulsive buying behavior. Moreover, impulsive buying is proven to mediate the relationship between these three variables and the intention to use e-commerce. These results highlight the importance of emotional factors and digital lifestyles as the main drivers of young consumers’ purchasing behavior and provide strategic insights for e-commerce platforms and the fashion industry in designing more effective and emotionally driven marketing strategies.